Lumbosacral angiolipoma: case report - Antonio Aversa do Souto; Flavio S. Domingues; Leila Chimelli; Armando M. Lemos (Arquivos de Neuro-Psiquiatria)
We present a case of a 46-year old woman with a ventral epidural angiolipoma at the lumbosacral level with erosion of the sacrum. About ninety cases of spinal angiolipomas have been previously described in the literature, most of them situated on the thoracic region, dorsal to the dural sac. Angiolipomas can be radically excised with a good prognosis even in the presence of bone erosion. We did not find any other angiolipoma at the sacral level surgically explored in the review of the literature.